The evaluation and implementation of magnetic fields for large strain uniaxial and biaxial cyclic testing of Magnetorheological Elastomers. (May 2016) - Gorman, Dave; Murphy, Niall; Ekins, Ray; Jerrams, Stephen
Abstract: Magnetorheological Elastomers (MREs) are "smart" materials whose physical properties are altered by the application of magnetic fields. In previous studies the properties of MREs have been evaluated under a variety of conditions, however little attention has been paid to the recording and reporting of the magnetic fields used in these tests [1]. Currently there is no standard accepted method for specifying the magnetic field applied during MRE testing. This study presents a detailed map of a magnetic field applied during MRE tests as well as providing the first comparative results for uniaxial and biaxial testing under high strain fatigue test conditions. Both uniaxial tension tests and equi-biaxial bubble inflation tests were performed on isotropic natural rubber MREs using the same magnetic fields having magnetic flux densities up to 206 mT. The samples were cycled between pre-set strain limits. The magnetic field was switched on for a number of consecutive cycles and off for the same number of following cycles. The resultant change in stress due to the application and removal of the magnetic field was recorded and results are presented.